Cašmah-i faiz̤ : tarjumah-i pandnāmah-i Ḥaz̤rat Šaiẖ Farīd-ad-Dīn ʿAt̤t̤ār. Tarjumah-i Maulavī ʿAbd-al-Ġafūr H̱ān Bahādur Nassāẖ - ʿAṭṭār, Farīd-ad-Dīn (Naval Kišor, 1914)
Urdu verse translation of Farīd-ad-Dīn ʿAt̤t̤ār's Pand Nāmah--a Mas̱navī in short sketches exemplifying specific mystical and ethical virtues such as silence, munificence, patience etc